Electrical storm after cardiac resynchronization therapy in a patient with nonischemic cardiomyopathy: Signal‐averaged vector‐projected 187‐channel electrocardiogram‐based risk stratification for lethal arrhythmia. Issue 6 (5th July 2013) - Nakai, Toshiko; Mano, Hiroaki; Ikeya, Yukitoshi; Sonoda, Kazumasa; Ashino, Sonoko; Okumura, Yasuo; Ohkubo, Kimie; Kunimoto, Satoshi; Kasamaki, Yuji; Watanabe, Ichiro; Hirayama, Atsushi; Nakai, Kenji
Abstract: We describe treatment of atrial flutter and electrical storm presenting as incessant ventricular tachycardia (VT) after implantation of a cardiac resynchronization therapy defibrillator (CRT‐D) in a patient with dilated cardiomyopathy. No prior arrhythmic event had occurred. Our treatment strategy, including amiodarone administration, was guided in part by signal‐averaged vector‐projected 187‐channel electrocardiogram (SAVP‐ECG)‐based risk stratification for ventricular arrhythmia. Corrected recovery time (RTc) dispersion and Tpeak‐end dispersion were used to evaluate transmural dispersion of repolarization. RTc and Tpeak‐end dispersion increased during the period of electrical storm. Values were improved 2 years after CRT‐D implantation, and the amiodarone was discontinued. The VT has not recurred despite discontinuation of the antiarrhythmic agent. SAVP‐ECG‐based risk stratification for ventricular arrhythmia proved useful for the management of antiarrhythmic therapy.